The University and trans-frontier studies - Portugal, María Luisa (2022)
We have just participated in the first International Conference on Frontiers Lineae Terrarum that gathered 350 researchers, experts and academics on frontier studies, from 30 places from around the world. During four days several issues linked with theory and inter-frontier politics.   The seminar allowed the discovery of two particular items: first, that we constitute an 'army' of academics involved in the search of a better live standard and a culture of peace, and second, the importance that academic work has acquired on those centres dedicated to research on trans-frontier processes.   The present essay aims to call the attention on the initiatives made in the US and Mexico, as well as in Peru and Ecuador, in order to exchange knowledge and experiences, elaborate institutional links to improve relation amongst this class of regions.